(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Urbanization as the term implies involves the familiar sociological concepts of acculturation, diffusion, assimilation, and even amalgamation — although it involves much more. When people acquire the roles, style of life, symbols, forms of organization, and cultural artifacts contrary to the characteristic of country, and when they share the meanings, values, and perspectives that are characteristically non rural. It logically follows that there are degrees of urbanization because certain religious and cultural values are so deep rooted as a part of Great tradition’ and therefore resistant to change. The term urbanization has been made more precise and meaningful by interpreting the aspects of diffusion and acculturation. Diffusion refers to the spread of culture either within the same society or in different societies. Urbanization may be manifest either as intra-society or inter-society diffusion, that is urban culture may spread to or may be acquired in various parts of same society or it may cross cultural or national boundaries and spread to other societies. It involves both borrowing and lending. On the other side of the diffusion coin is acculturation, the process whereby individuals acquire the material possessions, behavioural patterns, social organization and bodies of knowledge. It is in the back drop of this analogy, the study is aimed at the empirical analysis of urbanization in Jammu and Srinagar cities. The point of view is that of a student of sociology, although there are implications for other social science students and urban planners.